ANALISA UNJUK KERJA MOTOR INDUKSI 3 PHASA TERHADAP PENGARUH HARMONISA (THD) DENGAN PENAMBAHAN FILTER AKTIF MENGGUNAKAN MATLAB - Duarsana, I Nyoman; Rinas, I Wayan; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2021)
Operating non-linear loads can cause harmonic distortion, one of which is an induction motor. Harmonics can cause the system power quality content level to become worse. One way to reduce harmonics is with an active filter. Theemethodduseddin thissresearchhissthe Simulink method in Matlab. The addition of an active filter aims to reduceetheeharmonicccontent in thennetwork in order toosee theeeffect ofhharmonics onttthe performanceeeof the 3 phase induction motor on rotation and torque. The results of simulation analysis using Matlab show that active filters can reduce the harmonic content in the network compared to networks without using active filters. The decrease that occurred in THDI was 11.88% in the Rrphase, 11.87% in theeSsphaseaand 11.88% in the Ttphase with a load of 3 motors. There is no change in motor performance at rotation and torque, namely the rotation of 1498 Rpm and torque of 0.4682 Nm.